China and the Evolution of the Present Climate Regime - Carlo Carraro; Barbara Buchner (Fondazione Eni Enrico Mattei (FEEM), 2003)
The recent events that followed the US decision not to comply with the Kyoto Protocol seem to drastically undermine the effectiveness of the Protocol in controlling GHG emissions. Therefore, it is important to explore whether there are economic factors and policy strategies that might help the US to modify its current policy and move back to the Kyoto-Bonn agreement. For example, can an increased participation of developing countries induce the US to effectively participate in the effort to reduce GHG emissions? Is a single emission trading market the appropriate policy framework to increase participation in the Kyoto-Bonn agreement? This paper addresses the above questions by analysing whether the participation of China in the cooperative effort to control GHG emissions can provide adequate incentives for the US to move back to the Kyoto process and eventually ratify the Kyoto Protocol. This paper analyses three different climate regimes in which China could be involved and assesses the participation incentives for the major world countries and regions in these three regimes.
Keywords: C72; H23; Q25; Q28; 330; Agreements; Climate; Incentives; Negotiations; Policy; Umweltabkommen; Klimaschutz; Anreiz; Mitgliedschaft; China